DETERMINANTS OF HOUSEHOLD FOOD SECURITY: AN EVIDENCE FROM SMALL FARMER IN SWAMP AGROECOSYSTEMS IN CIAMIS, INDONESIA - Yusuf, Muhamad Nurdin (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Swamp agroecosystems are sub-optimal lands with distinctive characteristics, namely low fertility, and can only be planted once a year during the dry season. Small farmers whose primary income comes from the agricultural sector are becoming increasingly difficult due to climate-changing changes that can intimidate their household food security. This research aimed to analyze the factors that affect the food security of small farmer households in the swamp agroecosystem. The method used a survey of 247 farmers who run rice farming in swamp agroecosystems in the Ciamis Indonesia, which were determined randomly from a population of 648 farmers using the Slovin formula at an error rate of 5%. The research was analyzed by SEM (Structural Equation Models). The result showed that the factors impacting the food security of small farmer households in swamp agroecosystems came from farmer characteristics, income structure, and farm risk. Based on this, the development of small agro-industry in rural areas must be carried out to create household food security.